The International Criminal Court and the Place of Africa in International Justice System - Ofodeme, Juliet Amarachi; Nwali, Uche (American Journal of Humanities and Social Sciences, 2015)
Human rights have been flouted indiscriminately and deliberately in the international system. To that effect, the ICC was established to ensure that perpetrators of massive and systematic violations of human rights are brought to justice in the international system. The aim of this paper is to examine the effectiveness of the International Criminal Court in the discharge of its mandate in the global system. The central argument in the paper is that the ICC has made significant progress in the prosecution of some cases, but all in Africa. Meanwhile, there are cases within its jurisdiction that have been ignored in other parts of the world, especially when advanced countries are involved. Neoliberalism was adopted as the theoretical framework. The study adopted secondary method of data collection. The data was content analyzed. It was established that the ICC is faced with challenges and that the long term viability depends on how successfully it overcomes its challenges. This study advocates for: first, fairness in the UNSC referrals. Second, America’s taming of its unilateralism. Third, financial contributions without string attached. Fourth, United States ratification of the Rome Treaty; and fifth, ICC prosecution of all the cases within its jurisdiction in every part of the globe.